The Determinants of Fraud Prevention in Government Agencies - Nabila Maharani Safitri; Erry Andhaniwati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study is to examine the influence of the whistleblowing system, internal control, apparatus competence, and auditor ethics on fraud prevention in government agencies. A quantitative method is used in this study as a research approach. Meanwhile, the object of research is the auditor of BPKP (Financial and Development Supervisory Agency) Representative of East Java with the sample in this study totaled 112 internal auditors. This study uses the type of primary data in the form of a questionnaire by Google Forms given to the auditors. The data analysis used PLS-SEM with SmartPLS software version 4 as the analysis tool. The study’s results show that the whistle-blowing system and auditor ethics positively and significantly influence fraud prevention in government agencies, while internal control and apparatus competence do not significantly influence fraud prevention in government agencies.